A Proposed User-Generated Content (UGC) Strategy in Influencing Purchase Intention of Family Segment With Mediation of Perceived Usefulness and Perceived Trust - Aisyah Nuralam; Novika Candra Astuti (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
In the current era of social media utilisation, User Generated Content (UGC) has become a pivotal factor in influencing consumer behaviour, particularly with regard to purchase intention. The present study investigates the influence of UGC on purchase intention in the family segment, with a specific focus on mothers as primary household decision-makers. Utilising a quantitative approach with 152 respondents fitting the family demographic, the study applies Structural Equation Modeling Partial Least Squares (SEM-PLS) to examine the relationships among UGC, perceived usefulness, perceived trust, and purchase intention. The findings indicate that UGC exerts a substantial influence on both perceived usefulness and perceived trust. However, it is important to note that only perceived trust has a direct and mediating effect on purchase intention. Conversely, perceived usefulness, though positively influenced by UGC, does not significantly drive purchase decisions. Furthermore, UGC exerts a direct influence on purchase intention, thereby underscoring its persuasive power that extends beyond the realm of functional value. The findings of this study emphasise the pivotal role of trust in influencing purchasing decisions among family consumers, thereby underscoring its considerable potential impact on consumer behaviour. Consequently, marketing strategies should concentrate on generating credible, honest, and experience-based UGC to effectively target this segment.